PENINGKATAN HASIL BELAJAR PERMAINAN BOLA KECIL SISWA KELAS VB TUNARUNGU DENGAN MENGGUNAKAN PERMAINAN BOLA ADVENTURE DALAM PEMBELAJARAN PENJAS DI SDLB NEGERI PURBALINGGA TAHUN AJARAN 2013 / 2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning outcomes play small ball VB class deaf students using a ball game adventure in learning SDLB Purbalingga penjas in the academic year 2013/2014 . This study is an action research ( action research) because of research done to solve the problem of learning in the classroom . Observations on cycle 1 , ie psychomotor aspects gained 65.47 % , 80.95 % gain cognitive and affective aspects of acquiring 100 % . In the first cycle the average value reached 78.92 class that meets both criteria . While the results of observations of cycle 2 , the psychomotor aspects of gaining 74.99 % , 90.47 % gain cognitive and affective aspects of acquiring 100 % . . In the second cycle the average value reached 84.4 classes that meet the criteria very well. Based on the above results , concluded that Ball Adventure games can improve learning outcomes of small ball . Therefore Penjasorkes teachers are advised to use the game as an alternative learning Adventure Ball Small Ball in SDLB.